The Effect of Accounting Perceptions, Accounting Knowledge, and Motivation on the use of Accounting Information Systems in Petang District - PRATIWI, Anak Agung Trisna Dwi; KAWISANA, Putu Gede Wisnu Permana; AZIS, Ita Sylvia Azita (Journal of Governance, Taxation and Auditing, 2023)
This research was conducted based on differences in the focus of discussion on the influence of accounting perceptions, accounting knowledge of MSME actors, and motivation on using accounting information systems in Petang District. In addition, there are also research problems, such as the results of preliminary observations made at MSMEs in Petang District found phenomena such as running the system not always going well, there were human resources which were not ready to implement the system, so it took longer to implement it. This study aims to analyze and explain the effect of accounting perceptions, accounting knowledge of MSME actors, and motivation on the use of accounting information systems in the Petang District. This research was conducted in Petang District with a population of 41 SMEs and a sample of 35 SMEs with 70 respondents. All data obtained from the questionnaire distribution is feasible, then analyzed using multiple linear regression analysis processed with the SPSS 25.0 program. The results of hypothesis testing indicate that accounting perceptions have a positive and significant effect on usage system information accounting. The accounting knowledge of MSME actors has a positive and significant effect on usage system information accounting. Motivation has a positive and significant effect on usage system information accountancy.